Ageing and Learning Agility –Mediating role of learning perception and Moderating role of technology leverage. Issue 5 (2nd November 2021) - Deepa, V.; Sujatha, R.; Baber, Hasnan
ABSTRACT: The future of work requires continuous upskilling and reskilling of workers for full labour force participation and productivity that has led to growing importance of learning agility. However, research on this subject is still in its infancy. This study aims to investigate the effect of ageing on learning agility and mediating effects of perception of learning. The study also examines the moderating role of technology leverage on the relationship between perception of learning and learning agility. Partial least square (PLS) structural equation modelling (SEM) approach was used to analyse the data using SmartPLS 3.0 software. The data was collected from 377 working professionals using the snowball sampling technique. The results suggested that ageing and perception of learning has a significant positive impact on learning agility. However, there is no significant mediating effect of perception of learning on learning agility. The moderating effect of technology leverage was found to be insignificant on the interaction between perception of learning and learning agility. The study will be useful for learning platforms and human resource practitioners and managers to develop effective strategies for upskilling and reskilling their workers.